Co‐occurrence and phylogenetic distance in communities of mammalian ectoparasites: limiting similarity versus environmental filtering. Issue 1 (21st June 2013) - Krasnov, Boris R.; Pilosof, Shai; Stanko, Michal; Morand, Serge; Korallo‐Vinarskaya, Natalia P.; Vinarski, Maxim V.; Poulin, Robert
<x xml:space="preserve">Abstract</x> Similarity between species plays a key role in the processes governing community assembly. The co‐occurrence of highly similar species may be unlikely if their similar needs lead to intense competition (limiting similarity). On the other hand, persistence in a particular habitat may require certain traits, such that communities end up consisting of species sharing the same traits (environmental filtering). Relatively little information exists on the relative importance of these processes in structuring parasite communities. Assuming that phylogenetic relatedness reflects ecological similarity, we tested whether the co‐occurrence of pairs of flea species (Siphonaptera) on the same host individuals was explained by the phylogenetic distance between them, among 40 different samples of mammalian hosts (rodents and shrews) from different species, areas or seasons. Our results indicate that frequency of co‐occurrence between flea species increased with decreasing phylogenetic distance between them in 37 out of 40 community samples, with 14 of these correlations being statistically significant. A meta‐analysis across all samples confirmed the overall trend for closely related species to co‐occur more frequently on the same individual hosts than expected by chance, independently of the identity of the host species or of environmental conditions. These findings suggest that competition between closely related, and therefore presumably ecologically similar, species is not important in shaping flea communities. Instead, if only fleas with certain behavioural, ecological and physiological properties can encounter and exploit a given host, and if phylogenetic relationships determine trait similarity among flea species, then a process akin to environmental filtering, or host filtering, could favour the co‐occurrence of related species on the same host.